2021
DOI: 10.1111/cpr.13096
|View full text |Cite
|
Sign up to set email alerts
|

Base editing‐mediated perturbation of endogenous PKM1/2 splicing facilitates isoform‐specific functional analysis in vitro and in vivo

Abstract: Objectives PKM1 and PKM2, which are generated from the alternative splicing of PKM gene, play important roles in tumourigenesis and embryonic development as rate‐limiting enzymes in glycolytic pathway. However, because of the lack of appropriate techniques, the specific functions of the 2 PKM splicing isoforms have not been clarified endogenously yet. Materials and methods In this study, we used CRISPR‐based base editors to perturbate the endogenous alternative splicing of PKM by introducing mutations into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The protein expression of PKM1 was very low in DLBCL tissue. Recent study has reported that the expression of PKM1 tends to be cancer-specific and may have tumor-suppressive and tumor-promoting roles based on varying contexts [ 17 ]. Therefore, it is crucial to further investigate the expression and the role of PKM1 in DLBCL cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein expression of PKM1 was very low in DLBCL tissue. Recent study has reported that the expression of PKM1 tends to be cancer-specific and may have tumor-suppressive and tumor-promoting roles based on varying contexts [ 17 ]. Therefore, it is crucial to further investigate the expression and the role of PKM1 in DLBCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reversion of PKM1 to PKM2 is indispensable for shifting glucose metabolism toward aerobic glycolysis [ 16 ]. It has been reported that specific loss of PKM2 suppresses the growth of HCT116 cells [ 17 ]. An increased PKM2/PKM1 ratio has been observed in multiple cancer types and is significantly associated with poor overall survival (OS) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…HEK293T cells were transfected with 1,500 ng ancSgo-BE4 or ancSth1a-BE4, 500 ng gRNA (with a GFP indicator), and 100 ng target reporter using EZtrans reagents in 24-well plates, and three replicates were performed for each group. The cells obtained from cell sorting of GFP/mRuby double-positive cells using flow cytometry were subjected to lysis and PCR amplifications using Phanta Max SuperFidelity DNA polymerase (Vazyme; P505) as we previously described ( Lin et al, 2021 ). The target deep sequencing results for calculating the editing efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…PKM1 up-regulation in Ex10-mutant cells is corroborated by some degree of induced-whether new or enhanced-PKM1 expression in multiple cell types following PKM2 depletion. For example, PKM1 was upregulated in response to the following PKM2-targeting gene manipulations: CRISPR-guided base editing of the exon 10 3 0 or 5 0 SS in myoblasts, colon cancer cells and zebrafish embryos [26,27]; CRISPR/Cas9-induced double-strand break and mutation of exon 10 in breast cancer cells [28]; and Cre recombinase-mediated deletion of exon 10 in mouse embryonic fibroblasts [29]. However, when utilizing the same gene-editing technique, the extent of PKM1 induction could be tissue-or cell-specific.…”
Section: Mechanisms Of Discrepant Reciprocal Pkm Isoform Perturbationmentioning
confidence: 99%